Dinâmica das propriedades térmicas e do fluxo de calor no solo em uma área de pastagem no bioma Pampa - Zimmer, Tamíres (2017)
For the thermal characterization of a soil it is necessary to determine its thermal properties, because they describe how the storage and the propagation of thermal energy vary a function of time and depth. This knowledge is important to characterize the local microclimate, essential for studies of seed germination and plant growth. The objective of this study was to study the dynamics of thermal properties and soil heat flux in a pasture area in the Pampa Biome. In addition, two analytical methods were used to estimate soil heat flux: the amplitude method and the phase change method. All the estimates were made for different conditions of sky cover and soil moisture. The values of thermal conductivity, thermal diffusivity and volumetric thermal capacity are within the range of values found in the literature. Additionally, the soil properties presented dependence on soil moisture and different sky coverages. The differences between the experimental and the model results of soil heat flux were very small, suggesting that the two models are acceptable for estimating the soil heat flux. Therefore, the presented results provide subsidies for studies of ecological techniques suitable for the soil in the Pampa Biome.